Does pain in the masseter and anterior temporal muscles influence maximal bite force? - Goiato, Marcelo Coelho [UNESP]; Zuim, Paulo Renato Junqueira [UNESP]; Moreno, Amália; dos Santos, Daniela Micheline [UNESP]; da Silva, Emily Vivianne Freitas [UNESP]; de Caxias, Fernanda Pereira [UNESP]; Turcio, Karina Helga Leal [UNESP] (Elsevier, 2017)
Objective The aim of this study was to evaluate changes in pain and muscle force, and the relationship between them, in patients with muscle pain and bruxism, prior to and after treatment. Methods Thirty women with bruxism and myofascial pain (Ia) were included in this study. Sleep bruxism diagnosis was made based on clinical diagnostic criteria, and awake bruxism diagnosis was made by patient questionnaires and the presence of tooth wear. The diagnosis of myofascial pain was established according to the Research Diagnostic Criteria for Temporomandibular Disorders (RDC-TMD). Dentulous or partially edentulous patients (rehabilitated with conventional fixed prostheses) were included in the study according to the inclusion and exclusion criteria. The pain treatment protocol included occlusal splints, patient education, and physiotherapy for 30 days. Bite force was measured using a dynamometer at the central incisor and the first molar regions on both sides. The exams were performed at baseline, after 7 days, and 30 days after treatment. The Wilcoxon test was used to compare patient pain level response among the periods analyzed in the study. Bite force data were submitted to two-way repeated-measures ANOVA, followed by the Tukey HSD test (p < 0.05). A simple regression analysis was performed to verify the relation between pain level and bite force. Results Results revealed that there was a statistical difference in pain level over time for both muscles and sides (p < 0.01). In the molar region, the bite force exhibited significantly higher values after 30 days of treatment, when compared with the baseline (p < 0.001). There was a correlation between pain level and bite force only for the temporal muscle in all periods analyzed (p < 0.05). There was no strong correlation in the response level points to support the association of pain and bite force. Conclusions Pain level decreased and bite force increased in the molar region after treatment. No strong correlation or dispersion in the relationship between pain levels and bite force was seen in women with myofascial pain and bruxism.
Keywords: Bite force; Bruxism; Occlusal splints; Temporomandibular joint disorders